1994
DOI: 10.1017/s0022029900028442
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation oftransfatty acids in milk fat using spectroscopic and chromatographic methods

Abstract: Trans fatty acids (TFA) formed during biohydrogenation by ruminant animals were quantified in cows' milk fat by means of Fourier transform i.r. (FTIR) spectroscopy. When samples were analysed as the derived methyl esters, a spectral subtraction technique resulted in TFA values that were not biased by the unspecific absorption of intact triacylglycerols or influenced by the shape of the trans band. Austrian milk fat samples contained 20-50 g TFA/kg. Results obtained by analysis of TFA as triacylglycerols compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…This hypothesis was supported by identification in milk fat of two novel C18:2 isomers (i.e., trans-11, cis-15 C18:2 and cis-9, trans-13 C18:2) by Ulberth and Henninger (1994). Destaillats et al (2005) characterized cis-9, trans-11, cis-15 C18:3 and cis-9, trans-13, cis-15 C18:3 and concluded that the presence of these FA in rumen fluid, which definitely originate in small quantities from rumen metabolism, confirm the pathway reported in Fig.…”
Section: Conjugated Linolenic Acid Isomers Synthesis In the Rumenmentioning
confidence: 83%
“…This hypothesis was supported by identification in milk fat of two novel C18:2 isomers (i.e., trans-11, cis-15 C18:2 and cis-9, trans-13 C18:2) by Ulberth and Henninger (1994). Destaillats et al (2005) characterized cis-9, trans-11, cis-15 C18:3 and cis-9, trans-13, cis-15 C18:3 and concluded that the presence of these FA in rumen fluid, which definitely originate in small quantities from rumen metabolism, confirm the pathway reported in Fig.…”
Section: Conjugated Linolenic Acid Isomers Synthesis In the Rumenmentioning
confidence: 83%
“…III): trans-9 trans-12, cis-9 trans-13, cis-9 trans-12 and trans-9 cis-12 coeluting with trans-11 cis-15. These isomers were identified by comparing the relative retention times of the chromatographic peaks of the ewe's milk fat samples with the certified vegetable fats and with the milk fat chromatograms analyzed in similar chromatographic conditions in the literature [11,23,29].…”
Section: Octadecadienoic Isomersmentioning
confidence: 99%
“…Besides by FAME standards trans D9,trans D12, cis D9,trans D12, trans D9, cis D12 and cis D9,cis D12 (Sigma, St. Louis/Missouri, USA) the identification of trans-C18 : 2-isomers was done according to our earlier studies [35] which essentially were based on the studies of Ratnayake and Pelletier [41] and additionally on the work of Ulberth and Henninger [42].…”
Section: Identification Of Famementioning
confidence: 99%